Fewer Foreign Tourists Visit the Lublin Region - Józef Bergier; Michał Bergier (Barometr Regionalny, 2012)
The observation of changes in foreign tourist-visit-numbers in a particular region of a country is an important premise to analyze its tourist market and map out a strategy for development. The authors have made an analysis of foreign tourists visiting the Lublin Province in the years 2001-2010 considering their number, the purpose of their visits, their accommodation and the expenses they incurred. The analysis of the findings from the last decade has shown diminishing visits by foreign tourists in the Lublin Province in all the analyzed parameters.